PROYEKSI PERPUSTAKAAN DI LINGKUNGAN ISI SURAKARTA PADA ERA DIGITAL - Wahyu Karminah (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
ABSTRACT This study aims to reveal the study and evaluation of the ISI Surakarta library repository work system during the pandemic. It turns out that most of the users feel dissatisfied. Then find a representative model or breakthrough for the ISI Surakarta library repository work system in the face of a pandemic, by accommodating the library's electronic work system in online application-based services. Also recommends libraries to adopt big data systems in managing library collections, as well as updating the literacy needs of users at ISI Surakarta.